A Process for the Design and Development of Novel Bone Morphogenetic Protein-7 (BMP-7) Mimetics With an Example: THR-184 - William D. Carlson; William D. Carlson; William D. Carlson; William D. Carlson; Peter C. Keck; Peter C. Keck; Dattatreyamurty Bosukonda; Dattatreyamurty Bosukonda; Dattatreyamurty Bosukonda; Frederic Roy Carlson; Frederic Roy Carlson (Frontiers Media S.A., 2022)
Growth Factors have been evaluated as therapeutic targets for the treatment of a broad spectrum of diseases. Because they are proteins with pleiotropic effects, the quest to harness their beneficial effects has presented challenges. Most Growth Factors operate at the extracellular-receptor level and have natural feedback mechanisms that modulate their effects. As proteins, they are difficult and expensive to manufacture. Frequently proteins must be administered parenterally, may invoke an immune response, and may be neutralized by naturally occurring inhibitors. To circumvent these limitations, we have undertaken an effort to develop mimetics for the Bone Morphogenetic Protein (BMP) signaling pathway effects that incorporate the beneficial effects, eliminate the deleterious effects, and thereby create effective drug-like compounds.To this end, we have designed and tested a family of small peptide BMP mimetics. The design used the three-dimensional structure of BMP-7 to identify likely active surface regions. Lead sequences were then optimized based on in vitro assays that examine the selective binding to BMP receptors, demonstrate the phosphorylation of Smad-1,5,8, detect anti-apoptosis and anti-inflammation, and block the epithelial to mesenchymal transition (EMT) in renal tubular epithelial cells. These sequences were further optimized using in vivo assays of the attenuation of acute kidney injury in a rat-model of unilateral clamp ischemic reperfusion. This process uses a Structure Variance Analysis algorithm (SVA) to identify structure/activity relationships. One member of this family, THR-184, is an agonist of BMP signaling and a potent antagonist of TGFβ signaling. This small peptide mimetic inhibits inflammation, apoptosis, fibrosis and reverses epithelial to mesenchymal transition (EMT) by regulating multiple signaling pathways involved in the cellular injury of multiple organs. Its effects have been shown to control Acute Kidney Injury (AKI). THR-184 has progressed through phase I and II clinical trials for the prevention of Cardio-Vascular Surgery (CVS) associated AKI. This work provides a roadmap for the development of other growth factor mimetics and demonstrates how we might harness their therapeutic potential.